Molecular HPA genotyping by microarray in Brazilian blood donors. Issue 2 (13th June 2013) - Conti, Fabiana; Bertrand, Gerald; Dezan, Marcia; Costa, Thiago; Aravechia, Maria; Mota, Mariza; Castilho, Lilian; Kaplan, Cécile; Kutner, José
<x xml:space="preserve">Abstract</x> Background Human platelet antigens (HPA) polymorphisms may cause HPA alloimmunization, platelet (PLT) refractoriness, fetomaternal alloimmune thrombocytopenia, and posttransfusion purpura. Characterized by significant racial admixture, the Brazilian population might benefit from the knowledge about HPA frequency to guide decision‐making concerning PLT transfusion. Study Design and Methods HPA frequencies were determined in 158 DNA samples from Brazilian blood donors by microarray for HPA‐1 to ‐9, ‐11, and ‐15. A HPA‐2 discrepancy was solved by polymerase chain reaction with sequence‐specific primers (PCR‐SSP) and sequencing. Results While a alleles were predominant for HPA‐1 to ‐9 and ‐11, b alleles were absent for HPA‐6, ‐7, ‐8, and ‐11. HPA‐3 and HPA‐15 had a higher prevalence of ab genotypes. One case of HPA‐4ab and two cases of HPA‐9abw were detected, the latter not previously described in Brazilian blood donors. One sample was not interpretable for HPA‐2 due to a GPIb 468 C>G mutation; this donor was characterized as HPA‐2ab by PCR‐SSP and sequencing. Conclusion Allele frequencies were comparable to those described in other Brazilian studies. Rare HPA‐9 alleles were described in Brazilians for the first time. A mutation near the HPA‐2 polymorphism suggests that complementary methods might be necessary in specific cases. PLT genotyping by microarray proved to be fast, accurate, and reliable.